2015
DOI: 10.1007/s11427-014-4769-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane protein reconstitution for functional and structural studies

Abstract: Membrane proteins are involved in various critical biological processes, and studying membrane proteins represents a major challenge in protein biochemistry. As shown by both structural and functional studies, the membrane environment plays an essential role for membrane proteins. In vitro studies are reliant on the successful reconstitution of membrane proteins. This review describes the interaction between detergents and lipids that aids the understanding of the reconstitution processes. Then the techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Proteoliposomes based on large unilamellar vesicles (LUVs, from 50 to 400 nm) are promising systems for drug delivery, mainly owing to their size, hydrophobic/hydrophilic properties, biocompatibility, biodegradability and low toxicity in the human body [1721]. During the last decade, these biomimetic systems have gained interest as tools for biophysical studies of lipid–protein interactions as well as for biotechnological applications [16,22]. There is an increasing interest in the study and characterization of the structure, geometry, size and physical properties of proteoliposomes prepared for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Proteoliposomes based on large unilamellar vesicles (LUVs, from 50 to 400 nm) are promising systems for drug delivery, mainly owing to their size, hydrophobic/hydrophilic properties, biocompatibility, biodegradability and low toxicity in the human body [1721]. During the last decade, these biomimetic systems have gained interest as tools for biophysical studies of lipid–protein interactions as well as for biotechnological applications [16,22]. There is an increasing interest in the study and characterization of the structure, geometry, size and physical properties of proteoliposomes prepared for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…ClC-7 serves to transport Cl − across lysosomal membranes (Kasper et al, 2005; Lange et al, 2006; Graves et al, 2008). More recently, the large conductance Ca 2+ -activated K + (BK) channel, previously only known to work on the plasma membrane and mitochondria (Xu et al, 2002; Wang and Tonggu, 2015), was found to reside and function on endolysosomal membranes of several different cell types, especially nonexcitable cells that were not known to possess functional BK channels before (Cao et al, 2015b). Remarkably, BK is unlikely the only K + channel type present on these acidic organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane proteins are involved in various critical biological processes [65], which are believed to mediate attachment and invasion of Cryptosporidium . In the present study, our first identification of CpEno on the surface by immunofluorescence examinations indicates that this protein may be a membrane-related protein.…”
Section: Discussionmentioning
confidence: 99%